Development of novel aptasensor based carbon nano dots (CNDs) with FRET mechanism for detection of organophosphorus pesticides - Sriati Wahyudi; Ivan Rizoputra; Anas; Camellia Panatarani; Ayi Bahtiar (Applied Food Research)
Pesticide residues organophosphorus have always been a great threat to agricultural production and food safety. Herein, we developed a sensitive and selective sensing system for the detection of pesticides organophosphorus specific diazinon, malathion, and ethion. The system is based on the fluorescence resonance energy transfer (FRET) between carbon nano dots (CNDs) and nitrogen-sulfur CNDs (NS-CNDs) with gold nanoparticles (AuNPs). In this method, the fluorescence emission of CNDs was quenched by AuNPs due to FRET. When pesticides were added to the CNDs–AuNP system, the strong combination between thiol group and Au made the CNDs release from AuNPs, and the fluorescence of CNDs was recovered. Furthermore, aptamer can wrap AuNPs quench the fluorescence of CNDs. When pesticides are added, the aptamer is firstly consumed to preferentially combine with pesticides, resulting in the fluorescence recovery of CNDs from quenching status. The degree of fluorescence recovery is positively correlated with pesticide concentration, even with the addition of the aptamer, pesticide detection ability reaches nanomolar (nM) levels. This enables us to design a fluorescence aptasensor for sensitive detection of organophosphorus pesticides, especially diazinon and malathion. The proposed approach exhibits the advantages of high sensitivity, high selectivity, ease of procedure, and most importantly, low cost and non-cytotoxicity to detect organophosphorus pesticides.